Study on Fixed-Point Growth of Thermal Bubble with Micro-Planar Induction Heater - Liu, Bendong; Wang, Long; Zhang, Nailong; Liu, Haibin; Li, Desheng; Yang, Jiahui (Recent Patents on Mechanical Engineering, 2022)
Background: The thermal bubble-driven micro actuators have advantages of simple structure and low working voltage, which have broad prospects in the field of micro-fluidic systems. Methods: This paper presents a new type of micro-planar induction heater which can realize the fixed-point growth of thermal bubbles by adding some active cavities. The micro-planar induction heater is composed of a metal heating plate, a glass substrate, and a planar coil. Results: In the experiments, an alternating current of 80 kHz was applied to the micro-planar induction heater; both the heating time and the interruption time were 1 s controlled by a PLC. A CCD camera was used to record the generation process of thermal bubbles, including nucleation, growth, and shrinkage. The experimental results show that thermal bubbles can grow and contract periodically at the position of the cavities when the cavities diameter is 50 μm and 90 μm, respectively. The ideal thickness of the heating plate is between 6 μm and 13 μm. Conclusion: Here, the fixed-point growth of the thermal bubble with a micro-planar induction heater has been studied. This kind of fixed-point growth of thermal bubbles can be used in micro actuators, such as micro ejectors, micro mixers, and micro pumps.
Keywords: micro-heater